Effects of nematode-induced mechanical damage to the plantain root system under controlled conditions - Delgado Párraga, Alex (2021)
The vegetative development of the banana is exposed to biotic factors, including phytonematodes responsible for causing damage to the radical system, restricting water absorption, nutrients and affecting growth. The objective of this research work was to simulate the mechanical damage caused by the nematodes to the radical plantain system under controlled conditions. For the purpose, Barraganete meristematous plantain plants were used 45 cm high, sown in plastic sleeves with 40 L of pasteurized soil. The treatments consisted of washing plus elimination of 0, 25 and 50% of the radical mass plus an absolute control. Two months later, the weight of roots and growth were evaluated, observing significant differences, where the treatment with 0% root cut showed a lower weight (73.44 g) and height (53 cm), in relation to the other treatments with 155 g (on average) and 75 cm (on average). Possibly the handling of roots in 0% cutting were not sufficient to stimulate the mechanisms of defenses and growth of the plant.